Hyperuniformity with no fine tuning in sheared sedimenting suspensions - Jikai Wang (Nature Portfolio, 2018)
Suspensions appear in a wide range of industrial settings, and dispersing particles in a uniform manner throughout a fluid remains challenging for applications. Wang et al. obtain hyperuniform mixtures without fine tuning by harnessing self-organized criticality due to slow sedimentation and shear.